Pain transduction: a pharmacologic perspective. Issue 8 (2nd August 2016) - McEntire, Dan M.; Kirkpatrick, Daniel R.; Dueck, Nicholas P.; Kerfeld, Mitchell J.; Smith, Tyler A.; Nelson, Taylor J.; Reisbig, Mark D.; Agrawal, Devendra K.
ABSTRACT: Introduction: Pain represents a necessary physiological function yet remains a significant pathological process in humans across the world. The transduction of a nociceptive stimulus refers to the processes that turn a noxious stimulus into a transmissible neurological signal. This involves a number of ion channels that facilitate the conversion of nociceptive stimulus into and electrical signal. Areas covered: An understanding of nociceptive physiology complements a discussion of analgesic pharmacology. Therefore, the two are presented together. In this review article, a critical evaluation is provided on research findings relating to both the physiology and pharmacology of relevant acid-sensing ion channels (ASICs), transient receptor potential (TRP) cation channels, and voltage-gated sodium (Nav) channels. Expert commentary: Despite significant steps toward identifying new and more effective modalities to treat pain, there remain many avenues of inquiry related to pain transduction. The activity of ASICs in nociception has been demonstrated but the physiology is not fully understood. A number of medications appear to interact with ASICs but no research has demonstrated pain-relieving clinical utility. Direct antagonism of TRPV1 channels is not in practice due to concerning side effects. However, work in this area is ongoing. Additional research in the of TRPA1, TRPV3, and TRPM8 may yield useful results. Local anesthetics are widely used. However, the risk for systemic effects limits the maximal safe dosage. Selective Nav antagonists have been identified that lack systemic effects.